Can magnetic resonance imaging enhance the assessment of potential new treatments for cognitive impairment in mood disorders? A systematic review and position paper by the International Society for Bipolar Disorders Targeting Cognition Task Force. (22nd September 2022) - Miskowiak, Kamilla W.; Yalin, Nefize; Seeberg, Ida; Burdick, Katherine E.; Balanzá‐Martínez, Vicent; Bonnin, Caterina del Mar; Bowie, Christopher R.; Carvalho, Andre F.; Dols, Annemieke; Douglas, Katie; Gallagher, Peter; Hasler, Gregor; et al.
Abstract: Background: Developing treatments for cognitive impairment is key to improving the functioning of people with mood disorders. Neuroimaging may assist in identifying brain‐based efficacy markers. This systematic review and position paper by the International Society for Bipolar Disorders Targeting Cognition Task Force examines the evidence from neuroimaging studies of pro‐cognitive interventions. Methods: We included magnetic resonance imaging (MRI) studies of candidate interventions in people with mood disorders or healthy individuals, following the procedures of the Preferred Reporting Items for Systematic reviews and Meta‐Analysis 2020 statement. Searches were conducted on PubMed/MEDLINE, PsycInfo, EMBASE, Cochrane Library, and Clinicaltrials.gov from inception to 30th April 2021. Two independent authors reviewed the studies using the National Heart, Lung, Blood Institutes of Health Quality Assessment Tool for Controlled Intervention Studies and the quality of neuroimaging methodology assessment checklist. Results: We identified 26 studies ( N  = 702). Six investigated cognitive remediation or pharmacological treatments in mood disorders ( N  = 190). In healthy individuals, 14 studies investigated pharmacological interventions ( N  = 319), 2 cognitive training ( N  = 73) and 4 neuromodulatory treatments ( N  = 120). Methodologies were mostly rated as 'fair'. 77% of studies investigated effects with task‐based fMRI. Findings varied but most consistently involved treatment‐associated cognitive control network (CCN) activity increases with cognitive improvements, or CCN activity decreases with no cognitive change, and increased functional connectivity. In mood disorders, treatment‐related default mode network suppression occurred. Conclusions: Modulation of CCN and DMN activity is a putative efficacy biomarker. Methodological recommendations are to pre‐declare intended analyses and use task‐based fMRI, paradigms probing the CCN, longitudinal assessments, mock scanning, and out‐of‐scanner tests.